Insulin delivery to the brain using intracranial implantation of alginate‐encapsulated pancreatic islets. (27th January 2017) - Bloch, Konstantin; Vanichkin, Alexey; Gil‐Ad, Irit; Vardi, Pnina; Weizman, Abraham
Abstract: There is increasing evidence supporting a link between cognitive dysfunctions and impaired brain insulin signalling. Insulin therapy has previously been tested as an approach to ameliorate brain insulin resistance and deficiency in patients with various brain disorders. However, current strategies for insulin delivery to the brain may induce severe hypoglycaemia when injected peripherally or show poor uptake when delivered intranasally. Recently, we have shown that intracranial transplantation of naked pancreatic islets increased insulin content in the brain and attenuated cognitive dysfunctions without altering peripheral glucose homeostasis in rats with schizophrenia‐like syndrome. In this study, we show that intracranial implantation of 50 pancreatic islets encapsulated in disc‐shaped alginate is sufficient to elevate insulin content in the rat brain. Three weeks after implantation, the islets displayed intact morphology, intensive hormone staining and glucose‐sensitive insulin release. The ultrapure alginate with high guluronic acid content used for islet encapsulation demonstrated good biocompatibility and stability after intracranial implantation. All implanted animals were normoglycaemic and normoinsulinaemic. In conclusion, the intracranial implantation of a small amount of alginate‐encapsulated islets is an efficient tool for metabolically regulated insulin delivery to the brain. Copyright © 2017 John Wiley & Sons, Ltd.